Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÑƒÑÐ»Ð¾Ð²Ð¸Ð¹ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ Ð½Ð° ÑÐ¾Ñ…Ñ€Ð°Ð½Ð½Ð¾ÑÑ‚ÑŒ Ð¿Ñ€Ð¾Ð±Ð¸Ð¾Ñ‚Ð¸ÐºÐ° Lactobacillus plantarum - Zhelobetskaya, O. V.; Babinets, O. M.; Vysekantsev, I. P.; Ryazantsev, V. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
There was shown the possibility of cryopreserving an industrial strain of lactic-acid bacteria Lactobacillus plantarum in sucrosegelatine medium. It has been established that when freezing bacterial concentrate (5x1011 CFU/ml) the bacteria viability did not differ from the controland it was not affected by the media compositions and cooling protocols.